2015
DOI: 10.1021/acs.jpca.5b09933
|View full text |Cite
|
Sign up to set email alerts
|

Alkynes as CH/π Acceptors: Microwave Spectra and Structures of the CH2F2···Propyne and CH2ClF···Propyne Dimers

Abstract: Rotational spectra of weakly bound complexes of chlorofluoromethane (CH2ClF) and difluoromethane (CH2F2) with propyne (HCCCH3) have been measured using chirped-pulse and resonant-cavity Fourier-transform microwave spectroscopy, adding to a relatively small body of high resolution spectroscopic data on propyne complexes. Both dimers contain CH/π contacts, as well as secondary contacts between one or both halogen atoms and the methyl group of propyne. A detailed structural determination for CH2F2···propyne has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Fourier transform microwave (FTMW) spectroscopy, in particular, is an ideal tool for such investigations as the compound of interest is interrogated in a collision-free supersonic jet. A number of FTMW studies of weakly bound dimers involving small fluorinated molecules 5,6,7 have been reported in recent years but similar high resolution investigations of intramolecular interactions with fluorine are scarce. In such cases, the classification of an interaction as a hydrogen bond may be ambiguous as the optimal 180 o angle for X-H••• F may not be possible.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform microwave (FTMW) spectroscopy, in particular, is an ideal tool for such investigations as the compound of interest is interrogated in a collision-free supersonic jet. A number of FTMW studies of weakly bound dimers involving small fluorinated molecules 5,6,7 have been reported in recent years but similar high resolution investigations of intramolecular interactions with fluorine are scarce. In such cases, the classification of an interaction as a hydrogen bond may be ambiguous as the optimal 180 o angle for X-H••• F may not be possible.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the largest geometric changes were reported near the site of fluorination and these changes typically involved an increase in the ring angle at that site by 3–4° and a shortening of the adjacent C–C bonds by 0.005–0.010 Å. Although a number of studies of weakly bound dimers involving small fluorinated molecules have provided important insights into the nature of noncovalent interactions involving fluorine, the observation of these effects may be masked in intramolecular systems as the optimal 180° angle for X–H···F is often unfeasible . Despite these geometric constraints, however, recent studies of ortho fluorinated phenols and thiophenols have successfully identified subtle structural changes that are indicative of weak intramolecular forces involving F. These noncovalent interactions resulted in the stabilization of one planar conformer over the other.…”
Section: Introductionmentioning
confidence: 82%